Human development index of Bahau community - Ramli, Siti Aisyah; Md Yassin, Sulaiman; Abu Samah, Bahaman (TextRoad Publication, 2012)
To enhance the human development, the government has established a number of policies and facilities. All Malaysian have the opportunity to gain the benefits from such establishments. This study attempts to determine the level of human development among Bahau community. This study is a quantitative study and the respondents were chosen based on simple random sampling. A total of 300 respondents from Bahau were chosen to be surveyed. This study focuses on three parts which are 1) health; 2) income and 3) education. It was found that the human development index among Bahau community is at a moderate level. To further enhance their human development index, the government should provide opportunities for communities to increase their income and develop several new educational models to encourage and enable a new generation to explore new knowledge.